The Church in a secular age: a pneumatological reconstruction of Stanley Hauerwas's ecclesiology - Bjørndal, Silje Kvamme (Princeton theological monographs series, 2018)
How can the church navigate the challenges of our secular age? In The Church in a Secular Age, Norwegian and Pentecostal scholar Silje Kvamme Bjørndal takes on three dynamic thinkers, each in their own way, in search for insights to this question. Philosopher Charles Taylor offers the backdrop for the conversation, as Bjørndal carefully sifts out some of his most central tenets for understanding our secular age. Bjørndal then turns to the theologian and ethicist Stanley Hauerwas and critically engages his notion of the church as a community set apart from our secular age. By bringing several of Hauerwas's interlocutors into the conversation, Bjørndal manages to bring out both the acute relevance and the shortcomings of his ecclesiology. Thus, she finds that another turn is needed in order to offer a concrete, as well as creative, contribution to this ecclesiological conversation. Considering the undeveloped pneumatological undercurrent in Hauerwas's work, it proves fruitful to engage the leading Pentecostal scholar Amos Yong and his foundational pneumatology. This engagement results in a shift of agency, from the community to the Spirit. And keeping up the dialogue with Taylor's secular age, Bjørndal demonstrates how the Spirit's agency is crucial for the church as it attempts to navigate the particular challenges (and opportunities) of a secular age. - Back cover